1989
DOI: 10.1038/sj.bdj.4806794
|View full text |Cite
|
Sign up to set email alerts
|

A perspective of dental education in the twenty-first century

Abstract: With the beginning of the twenty-first century only twelve years away, it is clearly not too early for dental educators to be planning for it. If one compares the practice of dentistry and the nature of dental education in 1888 with that of 1988, and then tries to project what they will be like in the year 2088, we have a difficult task indeed. As Alvin Toffler has pointed out in his book Future Shock, we are in an ever escalating period of change. Dentistry and dental education will change much more in the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…16,17 This view is reinforced with evidence that, throughout the next century, dentistry and dental education are bound to change much more than they have changed over the past century. 2 Throughout the four stages of the consensusbuilding Delphi technique approach used in this study, participants identified various up-to-date scientific research trends within periodontics. However, in spite of that, items associated with some recent technological advances were not included in the final set of "indispensable" items.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 This view is reinforced with evidence that, throughout the next century, dentistry and dental education are bound to change much more than they have changed over the past century. 2 Throughout the four stages of the consensusbuilding Delphi technique approach used in this study, participants identified various up-to-date scientific research trends within periodontics. However, in spite of that, items associated with some recent technological advances were not included in the final set of "indispensable" items.…”
Section: Discussionmentioning
confidence: 99%
“…We are living in an ever-escalating period of change. 1,2 More than thirty years ago, Toffler 1 stated that the ability to deal with change would be society's most essential task.…”
mentioning
confidence: 99%
“…Recognition that technical skills alone are insufficient to ensure provision of inclusive and non-discriminatory dental care has supported calls for reform of educational curricula (Madhan et al, 2012), historically grounded in a view of disease as a function of individual (in)action (Allen and Finnegan, 1989). Whilst dentistry degrees increasingly incorporate courses designed to support development of the communication skills and thinking necessary to best "person centred" practice, there is scant evidence to inform interventions to enhance understanding of mental illness and reduce stigma amongst oral health care providers.…”
Section: Introductionmentioning
confidence: 99%